Verhandlungen der Gesellschaft für Erdkunde zu Berlin. - Boguslawski, Georg Heinrich von, 1827-1884; Reiss, W. (Wilhelm), 1838-1908; Güssfeldt, Paul, 1840-1920; Danckelman, Alexander Syvester Flavius Ernst, Freiherr von, 1885-1919; Kollm, Georg, 1846-1921 (Dietrich Reimer], 1874)
List of members in each volume.